The Use of Instagram as A Means of Indonesian Language Learning in Class VII SMP - Sari, Vira Sukma Permata; Markhamah, M (Universitas Muhammadiyah Surakarta, 2023)
The aim of this research is to describe the use of social media in Indonesian language learning used by teachers and students at school. It aims to determine the effectiveness of implementing this learning through the use of Instagram. Furthermore, it seeks to identify the obstacles students face in implementing learning in class VII Indonesian language lessons in junior high school. This research adopts a descriptive qualitative approach, utilizing data sources from documents, teachers, and students. Data collection was carried out through observation techniques, interviews, and documentation studies. The author employed a descriptive research design in conducting this research. This design was chosen to obtain actual research data about learning activities that occurred in class VII Indonesian language lessons in junior high school. The research results demonstrate that social media is highly beneficial in facilitating teaching and learning activities. During learning, students are expected to be independent in seeking out all information related to the subject matter. Overall, students' readiness was considered quite good as they were able to respond to assignments given via social media platforms, particularly Instagram.